Patriarchy and the cycle of violence: deconstructing the normalization of violence against women and children in Nagekeo - Mite, Petrus Selestinus (Trigin Publisher, 2025)
Cases of violence against children and women are one of the complex and certainly urgent social issues, especially for regions or regions with strong patriarchal social structures. Violence against women and children is not only influenced by patriarchal structures, but is also reinforced by cycles of normalization that perpetuate the practice as part of cultural